A Comparative Study of Product-Centric and Experience-Centric Value Creation in Indonesian Fashion Retail - Dian Prianka (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
This study examines how Indonesian fashion retailers strategically respond to the rising demand for physical, shareable experiences among digitally-native Generation Z and Millennial consumers. It aims to compare two distinct strategic approaches to value creation: “product-centricity” and “experience-centricity”; and to derive practical insights for navigating the contemporary experience economy. This study employs a qualitative comparative case study approach to investigate the distinct mechanisms of value creation. Through a comparative case study of the product-centric brand Colorbox and the experience-centric brand Paddy Playstore, this research analyzes their divergent value creation mechanisms using Aaker’s Brand Identity and Pine & Gilmore’s Experience Economy frameworks. Findings show Colorbox leverages its physical store primarily to support transactions of affordable apparel. In contrast, Paddy Playstore’s core offering is an immersive DIY experience, fostering value through co-creation and emotional engagement. The study concludes that both models are strategically viable, representing complementary strategic paths for retailers: layering experiential elements onto a product foundation or meticulously curating the core experience as the product itself.